A new species of Amaurobius C.L. Koch, 1837 (Araneae: Amaurobiidae) from Apennine Mountains (Italy) with the description of the male of A. pavesii Pesarini, 1991 - Ballarin, Francesco; Pantini, Paolo (Zootaxa, 2017)
A new species of the genus Amaurobius C.L. Koch, 1837, Amaurobius pesarinii sp. n., from the Apennine Mountains (Italy) is described on the basis of both sexes. The male of A. pavesii Pesarini, 1991, previously unknown, is also described. Females of A. pavesii and both sexes of the similar A. scopolii Thorell, 1871 are re-described. Detailed description of morphological characters allow clear separation between these species and the closely related A. ferox (Walckenaer, 1820). Their phylogenetic relationships among the most common Italian Amaurobius species are discussed on the basis of molecular data (partial fragments of the genes COI, 16S and H3), together with their distribution across the Italian Peninsula. This is the first contribution to a multi-locus phylogenetic tree of European Amaurobius species. The synonymy of A. sciakyi Pesarini, 1991 with A. ruffoi Thaler, 1990 is proposed based on morphological characters.